Analysis of the Role of Internal Audit in Enhancing Company's Internal Control - Sari, Dian Kartika (Manunggal Halim Jaya, 2022)
This study aims to explore the role of internal audit in enhancing a company's internal control system by examining internal audit practices, perceptions of internal control effectiveness, and the impact of internal audit recommendations. The research employs a qualitative approach, utilizing interviews and document analysis to gather data from participants representing various organizations. Results reveal significant variations in internal audit practices influenced by organizational size, industry dynamics, and regulatory frameworks. Despite these variations, internal audit functions universally serve as guardians of organizational integrity, providing independent assurance regarding internal control effectiveness. Participants expressed diverse perceptions of internal control effectiveness, citing resource constraints, inadequate training, and communication gaps as common challenges. However, internal audit was unanimously recognized as crucial in enhancing internal controls, offering independent assurance and promoting a culture of compliance and ethical behavior. Internal audit recommendations often led to tangible improvements in internal control systems, although challenges related to resource allocation and change management were reported. Theoretical implications highlight the multifaceted nature of internal audit functions and their critical role in organizational governance, while managerial implications emphasize the need for strategic resource allocation, prioritization, and change management initiatives. This research contributes to the understanding of internal audit practices and their impact on organizational effectiveness.